Procesos de preparación para tocar en vivo: relatos de guitarristas de excelencia - Iravedra, Rafael (2020)
Even though the process of learning a musical work is inseparable from the results that a performer will achieve on stage, it is possible to distinguish the process of learning a piece from that of preparing it for a live performance. This study presents the analysis of 23 interviews and questionnaires conducted with acclaimed classical guitarists about strategies for preparing for public performances. We applied three processes of qualitative analysis as developed by Miles and Huberman (1994), namely data reduction, data display and conclusion drawing. The results showed the importance of practicing performances (through performance simulation, informal performances and self-recording). Other important aspects regarding this topic were the creation of an artistic image of the piece, fingerings, visualization, memorization and pre-concert preparation.